Особливості соціального інтелекту курсантів, які навчаються в закладах вищої освіти зі специфічними умовами навчання - Харченко, С. В.; Kharchenko, S. V.; Svitlana Kharchenko (Право і безпека. – 2018. – № 4 (71). – С. 144-150, 2018)
Презентовано результати вивчення здібностей соціального інтелекту курсантів закладів вищої освіти зі специфічними умовами навчання в різні роки (інтервал між дослідженнями – 15 років) і різних курсів навчання. У них найчастіше діагностувався середній рівень соціального інтелекту, а найбільш розвинутою здібністю була здібність передбачати наслідки поведінки. Із часом у них відбулося певне зниження рівня здібностей соціального інтелекту, найменші зміни сталися із здібністю до логічного узагальнення й виділення загальних істотних ознак у різних невербальних реакціях людини.

It has been noted that the data on the development of the abilities of students’ social intelligence during their studies in higher education institutions, which are presented in the literature, are ambiguous and need to be clarified. The author of the article has analyzed the peculiarities of the abilities of social intelligence of cadets of institutions of higher education with specific learning conditions in different years (time interval between studies – 15 years) and at different courses. The research was conducted at Kharkiv National University of Internal Affairs in 2002 and 2017 by using J. J. Guilford’s Social Intelligence Methodology. 4 groups of cadets participated in the study. They were future psychologists who studied at 1, 3 (2 groups) and 5 courses. According to the results of the study, cadets are most often diagnosed with the average and lower than the average levels of social intelligence (high level of social intelligence among the surveyed cadets in 2017 was not diagnosed), the most advanced ability of social intelligence was the ability to predict the effects of behavior. The smallest changes over time were established regarding the cadets’ abilities to logical generalization, the allocation of common essential features in various nonverbal responses of a person. In general, there was a certain decrease in the level of the development of cadets’ abilities of social intelligence, especially the ability to understand the internal motives of people’s behavior; the author of the study suggests that this may be due to the negative influence of a number of factors in the social environment, where the abilities of social intelligence are formed. Among the factors that negatively affected the level of development of the abilities of social intelligence of the study participants, the author has distinguished the following: changes in child-parent communication; change in the content of education and attitudes towards children in secondary schools; reduction of the intensity of direct friendship communication and increase of the importance of communication in social networks. The author has proved the necessity to improve the educational and pedagogical conditions aimed at developing the abilities of social intelligence of modern professionals in the law enforcement sphere.

Представлены результаты изучения способностей социального интеллекта курсантов учреждения высшего образования со специфическими условиями обучения в разные годы (интервал между исследованиями – 15 лет) и на разных курсах обучения. У курсантов чаще всего диагностировался средний уровень социального интеллекта, а наиболее развитой способностью была способность предвидеть последствия поведения. Со временем у них произошло некоторое снижение уровня способностей социального интеллекта, наименьшие изменения произошли в уровне способности к логическому обобщению и выделению общих существенных признаков в разных невербальных реакциях человека.
Features of social intelligence of cadets trained in institutions of Higher Education with specific learning conditions
Особенности социального интеллекта курсантов, обучающихся в учреждениях высшего образования со специфическими условиями обучения
Keywords: Психологія. Рsychology. Психология; Юридична психологія. Legal psychology. Юридическая психология; Наукові публікації. Scientific publications. Научные публикации; соціальний інтелект; здібності соціального інтелекту; курсанти; курс навчання; рік навчання; заклади вищої освіти зі специфічними умовами навчання; social intelligence; social intelligence abilities; cadets; course of study; year of study; establishments of higher education with specific terms of studies; заведения высшего образования со специфическими условиями обучения; социальный интеллект; способности социального интеллекта; курсанты; курс обучения; год обучения; учреждения высшего образования со специфическими условиями обучения; Україна. Ukraine. Украина